2004
DOI: 10.1002/ajh.20230
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis associated with l‐asparaginase therapy and low fibrinogen levels in adult acute lymphoblastic leukemia

Abstract: L-Asparaginase is a chemotherapeutic agent commonly used in the treatment of both adult and pediatric acute lymphoblastic leukemia (ALL). A major complication is thrombosis, resulting from reduced synthesis of proteins such as antithrombin III. Hypofibrinogenemia, also a side effect, may be a marker of thrombosis and decreased protein synthesis. A retrospective chart review of identically treated patients revealed 9 thrombotic events among 93 patients (10%), 6 (7%) occurring during treatment cycles including L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 17 publications
(21 reference statements)
2
37
0
Order By: Relevance
“…19 Environmental risk factors for thrombosis are more frequent in adults than in children, but the only such factor clearly identified in our series was the use of oral contraceptives in women before induction. We did not, therefore, find any correlation between a very low Fg level (below 0.5 g/L) and thrombosis as previously reported, 20 not did we confirm the increased incidence of thrombosis in ALL patients with a T-cell immunophenotype. 21 Central venous catheters and genetic polymorphisms such as factor V Leiden and factor II 20210A have been associated with thrombosis in children, 22,23 but we did not systematically look for these hereditary risk factors in our adult population.…”
Section: Discussionsupporting
confidence: 37%
“…19 Environmental risk factors for thrombosis are more frequent in adults than in children, but the only such factor clearly identified in our series was the use of oral contraceptives in women before induction. We did not, therefore, find any correlation between a very low Fg level (below 0.5 g/L) and thrombosis as previously reported, 20 not did we confirm the increased incidence of thrombosis in ALL patients with a T-cell immunophenotype. 21 Central venous catheters and genetic polymorphisms such as factor V Leiden and factor II 20210A have been associated with thrombosis in children, 22,23 but we did not systematically look for these hereditary risk factors in our adult population.…”
Section: Discussionsupporting
confidence: 37%
“…In the literature, adverse drug reactions associated with L -asparaginase have often been related to a decreased hepatic protein synthesis, including ATIII and fibrinogen [6, 7,9,10,11]. In addition, L -asparaginase has been shown to induce micro- and macrovesicular steatosis of the liver [2, 8, 12, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of L -asparaginase include mainly hypersensitivity reactions, acute pancreatitis, coagulation disorders, immune suppression, and liver injury [4]. Coagulation disorders comprise hemorrhage and thromboembolic events [5,6,7,8,9,10] and are explained by impaired hepatic synthesis of coagulation factors such as antithrombin (AT) III, fibrinogen, and protein C. Bushman et al [11] suggested that low plasma concentrations of ATIII may be a consequence of a decreased translation and/or secretion of the protein in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Asparaginase is associated with an increased risk of vte 9,10 that is largely related to inhibition of hepatic protein synthesis, leading to decreased plasma levels of antithrombin and proteins C and S 11,12 . In all, increased age has been identified as a risk factor for vte, the incidence being 34% in adults compared with 5% in pediatric patients treated with asparaginase-containing regimens 13 .…”
Section: Introductionmentioning
confidence: 99%